Carbon sequestration and growth of Anthocephalus cadamba plantation in North Kalimantan, Indonesia - AGUS SARJONO; ABUBAKAR M. LAHJIE; B.D.A.S. SIMARANGKIR; R. KRISTININGRUM; YOSEP RUSLIM (Biodiversitas Journal of Biological Diversity, 2017)
Sarjono A, Lahjie AM, Simarangkir BDAS, Kristiningrum R, Ruslim Y. 2017. Carbon sequestration and growth of Anthocephalus cadamba plantation in North Kalimantan, Indonesia. Biodiversitas 18: 1385-1393. Forest plantation of Jabon (Anthocephalus cadamba) plays many important roles for the primary source of timber production and also the carbon absorption for environmental amelioration. The growth of A. cadamba trees was measured using the formulas of MAI (Mean Annual Increment) and PAI (Periodic Annual Increment) as the basis of the increment measurement, while the analysis of biomass and carbon with simple linear regression (y = a + bx) was used, with the coefficient of R2 = 0.90. The annual increment of A. cadamba trees reached its maximum point or the intersection between MAI and PAI at the age of 8 years, showing the maximum production of A. cadamba trees. Forest plantation of A. cadamba produced biomass and carbon sequestration of 81.90 ton ha-1 and 39.31 ton ha-1, respectively at the age of 8 years. However, the amount of biomass and carbon in another plot of A. cadamba trees was 96.85 ton ha-1 and 46.49 ton ha-1, respectively. While the values of the third plot were 116.84 ton ha-1 and 56.08 ton ha-1, respectively. The correlation between the diameter and biomass production and the correlation between the age of stands and carbon production were very strong with R2 value was higher than 0.90. This indicated that Jabon (Anthocephalus cadamba) plantation had important roles in carbon sequestration and biomass production.